Prevalence and correlates of soil-transmitted helminths in schoolchildren aged 5 to 18 years in low- and middle-income countries: a systematic review and meta-analysis - Agrawal, Ritik; Pattnaik, Sweta; Kshatri, Jaya Singh; Kanungo, Srikanta; Mandal, Nityananda; Palo, Subrata Kumar; Pati, Sanghamitra (Frontiers in Public Health, 2024)
Background According to the Global Burden of Disease (GBD) 2019 report, up to 1.5 million disability-adjusted life years (DALYs) are lost due to soil-transmitted helminths (STHs), and 5.9 million people are at risk of acquiring STHs. Regions with the highest prevalence of STH infections include Sub-Saharan Africa, China, South America, and Asia. While there are numerous fragmented studies on STH, comprehensive information on the prevalence and geographic distribution of different species, as well as their regional variations in the context of STHs is limited. The present systematic review and meta-analysis study attempts to provide a summary of the prevalence, geographical variation, and determinants of STHs among schoolchildren aged 5 to 18 years. Methods An extensive literature search was carried out using PubMed, Embase, Cinhal, and Psychinfo for studies published between 1999 and 2022 that reported the rate of STH infection in school-going children aged 5–18 years. A random effects model was employed in this meta-analysis due to expected heterogeneity. Subgroup analysis was carried out based on sex and STH species because of expected geographical variation. Results A total of 19,725 of the 49,630 children examined were infected with STH, yielding an overall pooled prevalence of 37.16% (95% CI: 29.74–44.89). The prevalence was highest in the Western Pacific region at 50.41% (95% CI: 33.74–67.04) followed by Europe at 39.74% (95% CI: 20.40–61.0) and Africa at 37.10% (95% CI: 26.84–47.95). Ascaris lumbricoides was found to be the most prevalent helminth with a prevalence of 24.07% (95% CI: 17.07–31.83). Conclusion The Western Pacific region is classified as a High-risk Zone (HRZ), while Southeast Asia, Africa, Europe, and the Eastern Mediterranean are classified as moderate-risk zones (MRZs). We found a 12% reduction in the pooled prevalence of STH infection from 1999 to 2012. Ascaris lumbricoides was the predominant species among schoolchildren. Mass Drug Administration (MDA) of Albendazole tablets and improved water, sanitation, and hygiene (WASH) practices are effective in controlling and preventing STH. Ensuring their implementation and access is crucial to addressing the problem. Systematic review registration https://www.crd.york.ac.uk/prospero/#loginpage, CRD42022333341.